Moving from Cognitive Loyalty to Behavioral Loyalty through Brand Romance: Evidence from Hotel Industry of Iran - Amir Khazei Pool; Farhad Hanifi; Vahid Reza Mirabi; Mohammad Javad Taghipourian (DETUROPE)
Brand romance is considered as a very important construct in marketing especially in brand area leading to the occurrence of some behaviors in consumers. However, a few types of research have been conducted on the importance of brand romance in hoteling. The present research aims to identify and test the effect of brand romance on four kinds of customer loyalty including cognitive loyalty, affective loyalty, conative loyalty and behavioral loyalty. The semi-structured interview was used to identify the measuring tool of brand romance. Then, customer loyalty questionnaire was added and distributed in the statistical society of the study. Data were tested using Smart-Pls2. Results of the research showed that brand romance had positive and significant effect on four kinds of loyalty. This research is a guide for hotel managers and marketers to perceive brand romance from viewpoints of customers. In addition, by applying suggestions, the research will help marketers create a stronger relationship between brand and customers and thus benefit from its outcomes.